Lord Cooke and Cambridge - Smith, ATH (Victoria University of Wellington Law Review, 2008)
This article seeks to explain the enduring formative influence that early life in Cambridge and at Gonville and Caius College exerted on Lord Cooke’s intellectual (and social) development. It suggests that his early experiences provided something of a platform which enabled Lord Cooke to take a leading part in the subsequent development of New Zealand’s separate legal identity.